Effect of texture on wear resistance of tantalum nitride film. (May 2019) - Tan, Pin; Fu, Licai; Teng, Jie; Zhu, Jiajun; Yang, Wulin; Li, Deyi; Zhou, Lingping
Abstract: The δ-TaN films were fabricated through reactive magnetron sputtering deposition technique onto WC-Co substrate. The texture of δ-TaN films can be tuned by adjusting the sputtering power and working gas pressure to vary the ion energy and mobility of particles. The underdense structure observed on film with (111) texture was formed at high work gas pressure and lower power due to large ion motion resistance and low driving force, respectively. Increasing ion mobility by decreasing pressure would lead to a fully dense δ-TaN (200) film with the lowest surface energy. The scratch test was used to measure the bond strength of the film to the substrate and how the film fails. The wear resistance of δ-TaN presented a strong correlation with texture. δ-TaN film with (200) texture possessed of lowest wear rate (2.4 × 10 −6 mm 3 /N·m) far below that of WC-Co (4.0 × 10 −6 mm 3 /N·m) and δ-TaN film with (111) texture (4.3 × 10 −6 mm 3 /N·m). δ-TaN film with (200) texture or no obvious texture had a hardness above 30 GPa, which was much higher than that of (111) texture. In addition, the lowest surface energy of (200) texture induced the mild adhesion between δ-TaN film and AISI52100 steel counterpart. So δ-TaN film with (200) texture had the best wear resistance among these films. Further study on the machinability behavior of δ-TaN films has been found to lead to more remarkable loss of wear volume of steel ball comparing with the WC-Co substrate. This film especially with (200) texture can be expected as an excellent candidate for cutting tools. Highlights: Variation in ion energy and mobility formed different texture of TaN films. (200) texture showed the best wear resistance and relative high hardness. The lower surface energy, the less adhesion mechanism occurred. δ-TaN(200) films with superior machinability can be the outstanding cutting tools.